Topical Application of Human Wharton's Jelly Mesenchymal Stem Cells Accelerates Mouse Sciatic Nerve Recovery and is Associated with Upregulated Neurotrophic Factor Expression. Issue 12 (December 2019) - Wang, Aline Yen Ling; Loh, Charles Yuen Yung; Shen, Hsin-Hsin; Hsieh, Sing-Ying; Wang, Ing-Kae; Chuang, Sheng-Hao; Wei, Fu-Chan
Peripheral nerve regeneration following injury is often slow and impaired, which results in weakened and denervated muscle with subsequent atrophy. Human Wharton's jelly mesenchymal stem cells (hWJ-MSC) have potential regenerative properties which, however, remain unknown in mouse nerve recovery. This study investigated the effect of the topical application of hWJ-MSC onto repairing transected sciatic nerves in a mouse model. Human adipocyte-derived stem cells (hADSC) were used as a positive control. The sciatic nerve of BALB/c mice was transected at a fixed point and repaired under the microscope using 10-0 sutures. hWJ-MSC and hADSC were applied to the site of repair and mice were followed up for 1 year. The hWJ-MSC group had significantly better functional recovery of five-toe spread and gait angles compared with the negative control and hADSC groups. hWJ-MSC improved sciatic nerve regeneration in a dose-dependent fashion. The hWJ-MSC group had a better quality of regenerated nerve with an increased number of myelinated axons throughout. hWJ-MSC appear to be safe in mice after 1 year of follow-up. hWJ-MSC also expressed higher levels of neurotrophic factor-3, brain-derived neurotrophic factor, and glial-derived neurotrophic factor than hADSC. hWJ-MSC may promote better nerve recovery than hADSC because of this upregulation of neurotrophic factors.